Prediction and prevention of crowd-crush accidents using crowd-density simulation based on unity engine - Chul-Ho Choi; Sung-Wook Park; Jun Park; Jong-Hoon Kim; Jin-Seong Kim; Hyun-Sung Yang; Bok-Eun Lee; Se-Hoon Jung; Chun-Bo Sim (Discover Applied Sciences)
Abstract This paper presents a crowd-density simulation system developed using the Unity engine to predict and prevent crowd-crush accidents. Crowd-crush accidents can occur in various environments where large crowds gather, often leading to significant casualties. Effective tools for risk assessment, training, and decision-making are crucial in preventing such accidents. The proposed simulator aims to provide a realistic virtual environment that accurately models crowd behavior and dynamics. By analyzing crowd density, flow patterns, and bottleneck situations, the simulator enables users to identify potential hazards, evaluate evacuation strategies, and develop proactive crowd management measures. The system incorporates advanced features such as real-time crowd visualization, interactive scenario creation, and data analytics. Validation experiments demonstrate the effectiveness of the simulator in predicting crowd-crush risks and supporting decision-making processes. The proposed solution enhances crowd safety and helps prevent accidents in various public-gathering scenarios.